2018
DOI: 10.1016/s2352-3018(18)30110-3
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care as an essential component of the HIV care continuum

Abstract: Although antiretroviral therapy has reduced mortality among people with HIV, inadequate treatment coverage, ageing, and the increasing incidence of organ failure and malignancies mean that high-quality care should include care at the end of life. This Review summarises the epidemiology of HIV in relation to mortality, and the symptoms and concerns of people with AIDS and those living with HIV who have either related or unrelated advanced comorbidities. In response to the evidence of a need for palliative care,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 72 publications
0
35
0
1
Order By: Relevance
“…Research on palliative care needs including end-of-life care and quality of care provided to PLHIV is underdeveloped [47]. The World Health Organization (WHO) has deemed that palliative care is an essential component of the comprehensive package of care for PLHIV.…”
Section: Gap 4: Palliative Care Needs Of Oalhiv Who Use Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on palliative care needs including end-of-life care and quality of care provided to PLHIV is underdeveloped [47]. The World Health Organization (WHO) has deemed that palliative care is an essential component of the comprehensive package of care for PLHIV.…”
Section: Gap 4: Palliative Care Needs Of Oalhiv Who Use Drugsmentioning
confidence: 99%
“…The World Health Organization (WHO) has deemed that palliative care is an essential component of the comprehensive package of care for PLHIV. Nevertheless, existing research points to inequitable access to palliative care among PLHIV [47]. People who use drugs are frequently restricted from accessing palliative care due to abstinence-based approaches adopted by many providers [48].…”
Section: Gap 4: Palliative Care Needs Of Oalhiv Who Use Drugsmentioning
confidence: 99%
“…Outside of India, however, palliative care is a recognised and essential component of the HIV care continuum. [24][25][26] Other illnesses are better represented in the Indian palliative care literature: for example, Lloyd et al recently conducted a qualitative study assessing the palliative needs of patients who had a stroke in a tertiary care setting in south India. 21 Despite only including clinicians in the study, the authors found that physical disabilities had the most significant impact on quality of life, and that palliative medicine played a major role in counselling and alleviating caregivers' burden in terms of stroke management and care.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, palliative medicine principles are essential to sustaining quality of life during aging. Providers and people aging with HIV need to consider how best to approach treatment preferences . For PLWH in resource‐poor areas, physical symptom burden may be similar to that experienced by patients living with cancer and requires careful symptom assessment and management.…”
mentioning
confidence: 99%
“…Providers and people aging with HIV need to consider how best to approach treatment preferences. 17 For PLWH in resource-poor areas, physical symptom burden may be similar to that experienced by patients living with cancer and requires careful symptom assessment and management. In all settings, person-centered care should address spiritual needs and psychological suffering.…”
mentioning
confidence: 99%